If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.2(x + 3) + -0.4(x + 3) = 0.2x + -0.6 Reorder the terms: 0.2(3 + x) + -0.4(x + 3) = 0.2x + -0.6 (3 * 0.2 + x * 0.2) + -0.4(x + 3) = 0.2x + -0.6 (0.6 + 0.2x) + -0.4(x + 3) = 0.2x + -0.6 Reorder the terms: 0.6 + 0.2x + -0.4(3 + x) = 0.2x + -0.6 0.6 + 0.2x + (3 * -0.4 + x * -0.4) = 0.2x + -0.6 0.6 + 0.2x + (-1.2 + -0.4x) = 0.2x + -0.6 Reorder the terms: 0.6 + -1.2 + 0.2x + -0.4x = 0.2x + -0.6 Combine like terms: 0.6 + -1.2 = -0.6 -0.6 + 0.2x + -0.4x = 0.2x + -0.6 Combine like terms: 0.2x + -0.4x = -0.2x -0.6 + -0.2x = 0.2x + -0.6 Reorder the terms: -0.6 + -0.2x = -0.6 + 0.2x Add '0.6' to each side of the equation. -0.6 + 0.6 + -0.2x = -0.6 + 0.6 + 0.2x Combine like terms: -0.6 + 0.6 = 0.0 0.0 + -0.2x = -0.6 + 0.6 + 0.2x -0.2x = -0.6 + 0.6 + 0.2x Combine like terms: -0.6 + 0.6 = 0.0 -0.2x = 0.0 + 0.2x -0.2x = 0.2x Solving -0.2x = 0.2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.2x' to each side of the equation. -0.2x + -0.2x = 0.2x + -0.2x Combine like terms: -0.2x + -0.2x = -0.4x -0.4x = 0.2x + -0.2x Combine like terms: 0.2x + -0.2x = 0.0 -0.4x = 0.0 Divide each side by '-0.4'. x = 0 Simplifying x = 0
| m-64.5=-7.1 | | 64b^3+1=0 | | -27=-253+x | | 13(t-3)+5t=6(3t+5)-8 | | 2/3g=4/9 | | 0=x^3+3x^2-24x-30 | | 28x^2-x-2=0 | | 5x-4=8y-3 | | 5n=20(4+.25) | | x^2+32x-126=0 | | -24=.263+x | | (3+3x)(6-x)=510 | | -39=x-62 | | 3-5(2+4x)=5 | | 12x-5=5x+23 | | 2x^2-x^2+1-4=0 | | 4cos^2x-3cosx=0 | | 5(a-12)-24=3(a+2) | | 2x^3-5x-69=0 | | 1.3(x+2)+5.6=17.3 | | x-3=-.5x+3 | | 5-9x=-4x | | 3z-2z+8= | | 3x+9=-1Y+29 | | 2x^3-5x-9=0 | | 12-42=3(x-2)-9 | | 100=33+x | | 15=(5k-13) | | 2x^2=1080 | | 32y^2+5y+6y= | | 40=-8(x+7) | | 700=84+28d |